Direct, diffuse and total solar radiation data set in La Guajira, Magdalena and Cesar departments -Colombia - Chamorro, Marley Vanegas (Data Brief, 2020)
This article aims to show direct, diffuse, and total solar radiation in the departments of La Guajira, Magdalena, and Cesar, located on the Caribbean coast of Colombia. In addition, data on climatic variables such as temperature, pressure, and relative humidity measured through different sensors located in these meteorological stations are presented. The data obtained by these stations correspond to measurements from 1993 to 2013 allowed the estimation of the parameters of the total, direct and diffuse solar radiation for each department, by mean of the Bird and Hulstrom model and parameterizations of the Mächler and Iqbal model. In addition, five climatological scenarios that could occur using these data were calculated.